INSTITUTIONAL ACTORS AS INTERNATIONAL LAW-MAKERS IN BUSINESS AND HUMAN RIGHTS: THE UNITED NATIONS GUIDING PRINCIPLES ON BUSINESS AND HUMAN RIGHTS - Letnar Černič, Jernej (Pravni zapisi, 2021)
Business and human rights is an interdisciplinary field, which advocates that both state and businesses are duty-holders of human rights obligations. The area of business and human rights aims to regulate and prevent negative impact of business operations at all levels of global supply chains. The approach of international law in this regard has so far been piecemeal. States have been traditionally a principal participant in the international community. Nonetheless, this article aims to test arguments submitted by Jovanović in his 2019 book “The Nature of International Law” that institutional non-state actors are capable of creating international legal rules. Equipped with this knowledge, this article argues that the UN Human Rights Council has through adoption of the UN Guiding Principles on Business and Human Rights restated human rights obligations of states and indirectly of corporations in international law in order to protect the dignity of rights-holders in local and global environments.